EXAMINATION OF ROMANTIC ATTACHMENT ACCORDING TO VARIOUS VARIABLES (Third Sector Social Economic Review, 2022)
A person is under the influence of the emotional, social and physical bond they establish with other people from the moment they are born until they die. A person's secure attachment directly affects life satisfaction and social relationships. But people connect in different styles. The aim of this research is to reveal the variables that affect romantic attachment. The research was designed in a quantitative design. As a data collection tool; A seven-point Likert ""Emotional Dependency Scale"" consisting of 9 items, which Karakurt conducted a validity and reliability study in 2001, was used. Research data were collected from 200 participants with random sample using the web survey method. The data were analyzed with the SPSS-25 program. Nonparametric tests (Mann Whitney-U and Kruskal Wallis-H) were preferred because the research data did not meet the normality condition. From the analysis of the research data, romantic attachment; It was found that the results differed depending on the variables of gender, marital status, economic level and having a child (p0.05). The fact that romantic attachment, which is one of the important factors in human life, was higher in married and child-bearing participants revealed the importance of the family institution. The higher rate of romantic attachment of male participants than female participants is an unexpected result of the study. Being attached as a developmental task in every period of his life directly affects the psychological and social mood of the person.
Keywords: Attach; Emotional Dependency; Confidence; Romantic Attachment; Intimacy